Risk Reduction Intervention Services for In-school Adolescents in the rural Areas of Abia State of Nigeria - E.E., Enwereji,; P.E.N, Onyemechi, (International Journal of Sexually Transmitted Diseases, 2021)
Introduction Risk reduction intervention is meant to provide enhanced and desirable interventions for HIV prevention among adolescents especially the in-school. Adolescents have been identified as the most vulnerable groups that can easily acquire human immunodeficiency virus (HIV) and other sexually transmitted diseases (STDs). Therefore, adolescents are the appropriate target for HIV prevention efforts. Most interventions for adolescents focus on providing AIDS-related education with the assumption that improving knowledge would enable adolescents to protect themselves from sexually transmitted infections. Numerous studies have shown that using class-room education alone is insufficient in reducing adolescents’ risky sexual behaviours. Therefore, this study used role-plays and peer facilitation for the study. Materials and Method The study used role-play and peer facilitation for the intervention strategy. The theme of the role-play was ‘My Future is My Choice’ (MFMC) intervention which was aimed to reduce HIV risk behaviours among sexually inexperienced adolescents. The role-play was carried out by 4 peer leaders who were trained in the theoretical framework of role-plays and peer facilitation by a consultant. With mastery and experience they carried out the role play in a regular classroom section for over 3 class periods, co-facilitated with the assistance of a volunteer teacher. A unique feature of this intervention was the dual focus on strategies that influenced both individual risk factors (i.e., attitudes, behavioural skills) and social environments (e.g., peer resources). A school was chosen by simple random sampling for the intervention. In the school chosen, a total sample of 65 students in senior secondary classes 2&3 ( SS2&3) were included in the study. These were the students considered to be sexually active who can respond to the questions in the questionnaire. Self-administered pre-and post-questionnaire were completed by the students. The results were analysed using frequency tables, descriptive and inferential statistics. Results The students studied were between the ages of 13-18 years. There was evidence that the role play ‘My Future is My Choice’ (MFMC) intervention created positive effects on reduction of HIV risk behaviours among the sexually inexperienced participants aged 13–18. Perceptions on methods of preventing risk reduction behaviours were also positively impacted by the intervention as 12(18.5%) and 34(52.3 %) of the respondents realized after post- intervention that having sex with someone outside marriage and being transfused with infected blood respectively Will constitute risk to HIV infection. Conclusion The role play which used the theme ‘My Future is My Choice’ (MFMC) intervention provided safer choices for reducing one or more measures of sexual risk behaviours among the sexual inexperienced respondents. It created the opportunity for the students to recognize that engaging in unprotected sex constitutes high risk for HIV, other sexually transmitted infections and pregnancy.
Keywords: abstinence; HIV risk-reduction intervention; sex partners; safer choices; pregnancy